Tuberkulosis Okular - Fabiola Supit (MEDICINUS, 2022)
Ocular tuberculosis (OTB) is a chronic disease caused by infection of M. tuberculosis in the eye with various manifestations and can lead to blindness. Indonesia has the second highest tuberculosis burden worldwide, with 11% of the case is extrapulmonary TB, including OTB. The most common clinical presentation of OTB is posterior uveitis, but it could also involve all surrounding ocular tissue. OTB has a good prognosis if patients receive full course of antituberculosis therapy, but there are so many challenges in the diagnosis and treatment initiation. There is a new international concensus published by the Collaborative Ocular Tuberculosis Study (COTS) working group which could aid clinicians to manage the disease.